Homelessness, Alcoholism, and Ethnic Discrimination among Alaska Natives - Travis, Robert (ARCTIC, 1991)
Homelessness among Alaska Natives is a social problem that currently plagues Anchorage, probably owing especially to the rapid social changes in rural Alaska following World War II. This study suggests that some Alaska Natives may be predisposed to homelessness after they have experienced relocation or social disruption during their high school years or problem drinking in their family of origin. A culture of poverty now appears to be reproducing itself in greater numbers than during the 1970s, when Alaska Native urban migrants were first studied. This subcultural context also appears to be reinforced by alcoholism and to a certain extent by ethnic discrimination, particularly in high school during adolescence and in the workplace during adulthood. Feeling discriminated against seems to foster anger, frustration, and self-blame among homeless Alaska Nativess, who often come to see themselves as outcasts within the urban centers far from their homeland.Key words: homelessness, culture of poverty, alcoholism, discrimination, Alaska Natives Mots clés: itinérance, culture de la pauvreté, alcoolisme, discrimination, autochtones alaskiens